Strategic integration of business process management and knowledge management in Warsaw Enterprises - Kowalczyk, Mateusz (Central Community Development Journal, 2023)
This study explores the integration of Business Process Management (BPM) and Knowledge Management (KM) in enterprises located in Warsaw, Poland, with a fo- cus on assessing implementation challenges, organizational culture, and the impact on performance. Drawing on qualitative and secondary data sources, this research highlights how BPM provides structural process optimization, while KM facilitates informed, agile decision-making. Findings indicate that while BPM and KM integra- tion is gaining traction, particularly in the business services and technology sectors, many small and medium-sized enterprises (SMEs) face significant barriers due to lim- ited resources, fragmented IT systems, and cultural resistance. However, the agility of SMEs and growing availability of institutional support offer considerable potential for transformation. Organizational culture has emerged as a critical success factor, where openness to collaboration, continuous learning, and digital readiness underpin successful integration. The study concludes with actionable policy recommendations for public and private stakeholders to enhance BPM-KM practices through capac-  ity building, digital literacy, and strategic alignment, thereby fostering innovation, resilience, and sustainable growth in Poland’s evolving knowledge economy.